2004
DOI: 10.1074/jbc.m406003200
|View full text |Cite
|
Sign up to set email alerts
|

High Dissociation Rate Constant of Ferrous-Dioxy Complex Linked to the Catalase-like Activity in Lactoperoxidase

Abstract: Heme reduction of ferric lactoperoxidase (LPO) into its ferrous form initially leads to the accumulation of the unstable form of LPO-Fe(II), which spontaneously converts to a more stable species, the two of which can be identified by Soret peaks at 440 and 434 nm, respectively. Our data demonstrate that both LPO-Fe (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 62 publications
2
15
0
Order By: Relevance
“…Several studies have indicated that this inactivation is, in fact, partially reversible. Ghibaudi and Laurenti (2003) propose that compound-III is able to reduce both compound-I and -II, and Galijasevic, Saed, Diamond, and Abu-Soud (2004) provide data that support the notion that compound-III can be formed during steady-state catalysis and suggest that the role of its formation and decay is the removal of an excess of hydrogen peroxide. Another mechanism by which a peroxidase removes excess amounts of hydrogen peroxide is catalase activity.…”
Section: Biochemistry and Mechanism Of Lactoperoxidasementioning
confidence: 75%
“…Several studies have indicated that this inactivation is, in fact, partially reversible. Ghibaudi and Laurenti (2003) propose that compound-III is able to reduce both compound-I and -II, and Galijasevic, Saed, Diamond, and Abu-Soud (2004) provide data that support the notion that compound-III can be formed during steady-state catalysis and suggest that the role of its formation and decay is the removal of an excess of hydrogen peroxide. Another mechanism by which a peroxidase removes excess amounts of hydrogen peroxide is catalase activity.…”
Section: Biochemistry and Mechanism Of Lactoperoxidasementioning
confidence: 75%
“…Purity of isolated MPO was established by demonstrating a Reinheitzhal (RZ) value of >0.85 (A 430 /A 280 ), SDS PAGE analysis was achieved with Coomassie blue staining, and in-gel tetramethylbenzidine peroxidase staining to confirm absence of observable contaminating eosinophil peroxidase activity [45]. Enzyme concentration was determined spectrophotometrically utilizing extinction coefficients of 89,000 M −1 cm −1 /heme of MPO [46]. …”
Section: Enzyme Purificationmentioning
confidence: 99%
“…Experiments were initially performed under conditions identical to those recently reported for MPO and other related hemoproteins to facilitate comparison [46][47][48]. Measurements were carried out under an aerobic atmosphere at 10 °C following rapid mixing of equal volumes of an H 2 O 2 -containing buffer solution and a peroxidase solution that contained 100 mM Cl − and/ or different Trp concentrations.…”
Section: Rapid Kinetic Measurementsmentioning
confidence: 99%
“…The amount of MLT used (100 μM) in the current work is sufficient to inhibit MPO. Studies on the effect of MLT on HOCl production by neutrophils and purified MPO have showed that the concentration of MLT that inhibited HOCl production by 50% (IC 50 ) was estimated to be 18 μM and reduced to 4 μM when superoxide was removed by addition of superoxide dismutase [52]. In contrast, the IC 50 value, calculated from the initial rate of H 2 O 2 consumption as a function of the MLT concentration was 3 μM [17].…”
Section: Discussionmentioning
confidence: 99%